TIRTA DALAM UPACARA PITRA YADNYA UMAT HINDU DI DESA BATU PUTIH KECAMATAN DUSUN TENGAH KABUPATEN BARITO TIMUR (Kajian Sosio Religius) - govinda, ardika (Widya Katambung, 2023)
Tirta or holy water is the main means of religious ceremonial activities for Hindus, as well as believed to be a medium of cleansing (pemarisudha) divine grace water (wangsuh pada) as holy water called tirta. In the context of yadnya the use of tirta as a means of pitra yadnyaceremony because of its function and meaning, then tirta in the pitra yadnya ceremony is studied using a socio-religious perspective that is routinely used by Hindus. The problem of what tirta is used in the pitra yadnya ceremony and how socioreligious tirta is in the pitra yadnya ceremony for Hindus in Batu Putih Village, Central Hamlet District, East Barito Regency, is analyzed using phenomenological and religious theories.Qualitative data on tirta used and reviews from socio-religious perspectives sourced from primary data and skunder data obtained by data collection techniques using observation, interviews and documentation analyzed using analytical methods when researching, reducing data, presenting and drawing conclusions.The result of the study is that water that has been matrai by Sulinggih or Regent is called tirtha "penglukatan" or cleansing of oneself as well as a medium for cleaning the facilities and infrastructure of the pitra yadnya ceremony requested in pelinggih or places considered sacred by Hindus. This kind of tirtha tirta "grace" because of its purity or spiritual power is believed to come from Ida Sang Hyang Widhi Wasa/God Almighty in His various manifestations worshipped at pelinggih or holy places. Socio-religious studies and religious analysis of water as a symbol of physical and spiritual purification (tirtha), called amertha, is as the water of life, has a meaningful role and position in all spheres of life. Tirta has an important position and role in implementing the form of sacrifice (yadnya), tirta or holy water is a means that implications for the coolness of life both individually and in groups, so that this implementation will give birth to good thoughts, good words and good deeds in a directed manner in carrying out life.